Empowerment of Ultra Micro MSME’s Through Financing of Sharia Non-Bank Financial Institutions - Ahmad Harun Arrasyid Nst; Muhammad Syahbudi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Economic growth, especially MSMEs, cannot be separated from the role of the microfinance institution sector. Financial institutions are intermediation institutions whose function is to connect parties who have excess funds with parties who lack funds. Based on Law No.10 of 1998 concerning amendments to Law No.7/1992 concerning banking, bank financial institutions consist of commercial banks and people's credit banks. The Ministry of Finance of the Republic of Indonesia, issued Ultra Micro Financing Products (UMI) which are The advanced stage program from the social assistance program to business independence targets micro businesses at the lowest levels, which cannot yet be facilitated by banking through People's Business Credits. UMI is a maximum financing facility of IDR 20 million per customer group and is distributed by non-bank financial institutions (LKBB). This research was carried out in North Sumatra (SUMUT) with the aim of identifying differences between Ultra Micro (UMi) business actors before and after receiving financing assistance from sharia non-bank financial institutions. This research was carried out between June and August 2023. This research uses quantitative analysis methods. The Normality Test is carried out with the aim of finding out whether the data used in a regression model is normally distributed or not. If the distributed data is proven to be normal, this means that the sample used can represent the population used by the measurement. If the significant value is 0.05, it can be declared to have a normal distribution. From the results of research on the Empowerment of Ultra Micro MSMEs through Sharia Non-Bank Financial Institution Financing in North Sumatra before and after receiving Ultra Micro Financing (UMi): There is a development between daily income before and after financing. Sales revenue after getting financing is better than sales revenue before getting financing